Perbandingan Uji Performa Impala dan Hive-Hadoop - Dede Kusuma; Aviarini Indrati (Syntax Corporation Indonesia, 2024)
The amount of data that is growing rapidly today also requires fast storage. This is because the need for data is also very important, and to access the data also requires fast time. Therefore, it is necessary to know the tools that support the processing of large amounts of data and fast time. The presence of Impala and Hive-Hadoop helps in making decisions about which tools to use to store data and quickly get the data needed. In this analysis and comparison, we want to know how the performance of these two tools is, namely whether Impala and Hive-Hadoop can access structured data. This research was conducted using experimental methods and manipulating the experimental environment using computer virtualization. The analysis results obtained are, Impala is faster than Hive-Hadoop because it reduces latency and Impala is not based on the MapReduce algorithm.